2008
DOI: 10.1002/anie.200705263
|View full text |Cite
|
Sign up to set email alerts
|

Valence‐Tautomeric Metal–Organic Nanoparticles

Abstract: Metal–organic nanoparticles (see SEM image) showing valence‐tautomeric behavior have been obtained by a versatile approach involving precipitation and coordination polymerization. They undergo reversible temperature‐dependent interconversion between low‐ and high‐spin forms, as revealed by plotting the magnetic moment χ as a function of temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(79 citation statements)
references
References 62 publications
2
76
1
Order By: Relevance
“…7,26 When the crystal was illuminated, light-induced change in charge distribution occurredknown as ligand-to-metal charge transfer (LMCT)so that the complex unit along the chain direction underwent an elongation of the Co−N bond and thus an anisotropic expansion of the crystal volume. Recently, an interesting VT complex, [Co III (3,5-DBCat)(3,5-DBSq)(bipy)] (bipy = 4,4′-bipyridine), 27 was obtained, which confirmed the strategy of using bridging ligand to achieve functional materials in the nanoparticle-formation process. This complex showed an abrupt VT transition near room temperature.…”
Section: ■ Introductionmentioning
confidence: 73%
“…7,26 When the crystal was illuminated, light-induced change in charge distribution occurredknown as ligand-to-metal charge transfer (LMCT)so that the complex unit along the chain direction underwent an elongation of the Co−N bond and thus an anisotropic expansion of the crystal volume. Recently, an interesting VT complex, [Co III (3,5-DBCat)(3,5-DBSq)(bipy)] (bipy = 4,4′-bipyridine), 27 was obtained, which confirmed the strategy of using bridging ligand to achieve functional materials in the nanoparticle-formation process. This complex showed an abrupt VT transition near room temperature.…”
Section: ■ Introductionmentioning
confidence: 73%
“…Imaz et al [206], reported the synthesis of [Co III (BIX)(3,5-DBSQ)(3,5-DBCAT)] n MOF nano-and microparticles via fast water-assisted precipitation from an ethanolic solution containing Co(OAc) 2 ·4H 2 O, 3,5-di-tert-butyl-1,2-catechol (3,5-DBSQ and 3,5-DBCAT are semiquinonate radical and catecholate forms of 3,5-di-tert-butyl-1,2-benzoquinone, respectively; BIX is 1,4-bis(imidazol-1-ylmethyl)benzene). MOF particle size could be tuned by regulating the rate of water addition (initiation solvent) to the reaction mixture.…”
Section: Initiation Solventmentioning
confidence: 99%
“…[80,81] Alternatively, NMOF particles can be generated by adding a poor solvent to a precursor solution containing MOF reaction components. [82][83][84] However, rational design of structures, in terms of shape, chemical composition and functionality for specific applications, remains a challenge. Here follow a few recent highlights from this area.…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%